Phosphorus-rich structures and capsular architecture in Cryptococcus neoformans. (March 2017) - Ramos, Caroline L; Gomes, Fabio M; Girard-Dias, Wendell; Almeida, Fernando P; Albuquerque, Priscila C; Kretschmer, Matthias; Kronstad, James W; Frases, Susana; de Souza, Wanderley; Rodrigues, Marcio L; Miranda, Kildare
Aim: In this study, we aimed to analyze the relationship of phosphorus-rich structures with surface architecture in Cryptococcus neoformans .Methods: Phosphorus-rich structures in C. neoformans were analyzed by combining fluorescence microscopy, biochemical extraction, scanning electron microscopy, electron probe x-ray microanalysis and 3D reconstruction of high pressure frozen and freeze substituted cells by focused ion beam-scanning electron microscopy (FIB-SEM).Results & conclusion: Intracellular and surface phosphorus-enriched structures were identified. These molecules were required for capsule assembly, as demonstrated in experiments using polysaccharide incorporation by capsule-deficient cells and mutants with defects in polyphosphate synthesis. The demonstration of intracellular and cell wall-associated polyphosphates in C. neoformans may lead to future studies involving their participation in both physiologic and pathogenic events.